Non-print Periodicals in the Wroblewski Library: what does the Collection Tell us about the History of Publishing in Lithuania? - Cicėnienė, Rima (Knygotyra, 2024)
In Lithuania, non-print periodicals have been of interest to scholars, librarians, and local historians for over a hundred years. To understand the phenomenon of non-print periodicals in Lithuania, its place in the increasing national information flow, and the history of state publishing, it is necessary to gather as extensive a base of these periodical sources as possible and know the main collections. This article aims to present the study of the non-print periodicals collection stored in the Manuscripts Department of the Wroblewski Library of the Lithuanian Academy of Sciences from the perspective of book science and reveal its informativeness as a whole for the history of Lithuanian publishing. The research object became all the identified non-print periodical publications collected into a conditional collection regardless of chronological frameworks, language, writing system, font, or publishing geographic location. Currently, the Manuscripts Department has recorded as many as 154 titles of small newspapers. To achieve the goal, first, historiography dedicated to non-print periodicals in Lithuania and the Wroblewski Library will be discussed, the history of object collection in the library will be determined, and the formed collection will be analysed in chronological, geographical, linguistic, typological, and genre aspects. The study of the information recorded in the publications’ metrics and texts provided insights into the processes of non-print publishing and allowed for comparisons with the processes of professional periodicals publishing. The history of the collection led to another multilingual collection of non-print periodicals covering the period between the late 19th century to 1946 in the Manuscripts Department of the Wroblewski Library, different in composition from the collection in the Rare Books and Old Periodicals Department. The analysis of the collection’s composition by designated aspects confirms the linguistic, genre, and typological diversity of publications that existed in Lithuania. The study allows us to state that although published in small volumes, non-print periodicals approached professional ones and contributed to the national information flow, filling informational and content gaps. They became a space for young creators to unfold and demonstrate practical knowledge, showcasing the potential of non-print periodicals publishing activities, which nurtured more than one professional press figure in Lithuania. The objects of the collection testify to the diversity of periodical publishing practices, and social groups involved in the publishing processes, and reveal the changing society and its aspirations. The collection gathered for the study provides new, unused information for scientific research on the reading and creativity of young people and soldiers, revealing their areas of interest. The collection’s objects become a relevant source for research on language, art history, gender, issues of the reuse of works, etc.
Keywords: non-print periodicals; publishing history; Wroblewski Library of the Lithuanian Academy of Sciences; newspapers; magazines; bulletins; one-time publications; manuscript newspaper; hectography; mimeography